2018
DOI: 10.7897/2230-8407.0911280
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound Promoted One Pot Synthesis of 1,5-Benzothiazepines Using Polyethylene Glycol (Peg-400)

Abstract: Synthesis of a variety of 1,5-benzothiazepines using polyethylene glycol PEG-400 as a medium and promoter. The synthesis is carried out using ultrasonic irradiation. The advantage of this protocol is that it eco-friendly, mild reaction conditions and the synthesis highlights the use of ultrasound irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Early works have been reviewed in 2005. , Since then, much progress has been made. Especially, one-pot synthesis type reactions, where many different components react in one step, have been successfully carried out in PEG due to its ability to dissolve a wide range of compounds. In fact, PEG can also dissolve mineral salts, , a contributing factor for its successful use as the reaction medium for the synthesis of metal–organic frameworks . Pd-catalyzed reactions (the importance of these can be seen in the 2010 Nobel prize award for their discovery) have also been carried out in PEG under both homocatalytic and heterocatalytic conditions where Pd is immobilized onto a porous silica material. PEGs have also been successfully used as components in deep eutectic solvents. Despite all of these successes, there are only limited experimental and theoretical studies on the dynamics of neat PEG. Experimental physicochemical properties of PEGs are needed to further this effort.…”
Section: Introductionmentioning
confidence: 99%
“…Early works have been reviewed in 2005. , Since then, much progress has been made. Especially, one-pot synthesis type reactions, where many different components react in one step, have been successfully carried out in PEG due to its ability to dissolve a wide range of compounds. In fact, PEG can also dissolve mineral salts, , a contributing factor for its successful use as the reaction medium for the synthesis of metal–organic frameworks . Pd-catalyzed reactions (the importance of these can be seen in the 2010 Nobel prize award for their discovery) have also been carried out in PEG under both homocatalytic and heterocatalytic conditions where Pd is immobilized onto a porous silica material. PEGs have also been successfully used as components in deep eutectic solvents. Despite all of these successes, there are only limited experimental and theoretical studies on the dynamics of neat PEG. Experimental physicochemical properties of PEGs are needed to further this effort.…”
Section: Introductionmentioning
confidence: 99%
“…[19] One way to achieve this is by looking at alternative catalysts that can be re-used (e. g., Co 3 O 4 nanosheets [45] or H-Fer zeolites), [46] are non-toxic and cheaper (e. g., saturated ammonium chloride solution in water [10] or mango juice), [47] can be used in one-pot tandem reactions (e. g., nanocrystalline ZSM-5) [48] or either do not require the use of any solvent, or can be used with water as the solvent (e. g., tetra-n-butylammonium fluoride (TBAF) [49] or Na 2 CO 3 / tetrahexylammonium chloride (THAC) in water). [47] Another way to pursue greener approaches is to employ a different solvent that can be recycled and that allows for mild reaction conditions, such as hexafluoropropan-2-ol [50] and polyethylene glycol in combination with ultrasound irradiation, [51] or a biodegradable and non-toxic solvent, such as glycerol. [52] Lastly, ionic liquids can be considered as another green alternative as they can be re-used, can reduce the reaction time and can help to reduce the need of harmful catalysts.…”
Section: Synthesis Of 15-benzothiazepanes Through Reaction Of αβUnsat...mentioning
confidence: 99%
“…Thanks to the success of the previous reaction, Kannan and co-workers extended the synthetic process to indole-based chalcones by reacting them with different carbohydrazides following the same ultrasonication conditions reported above ( Kannan et al, 2019 ). Finally, a one-pot cyclo condensation reaction was performed between chalcone derivatives and o -aminothiophenol by Devkate et al In their approach, several solvents were tested and PEG-400 was identified as the best choice providing a shorter reaction time and straightforward separation procedures for the target 1,5-benzothiazepines ( Devkate et al, 2018 ).…”
Section: 1 Ultrasound Chemistrymentioning
confidence: 99%